Persistent Racial Disparities in Utilization Rates and Perioperative Metrics in Total Joint Arthroplasty in the U.S.: A Comprehensive Analysis of Trends from 2006 to 2015 - Amen, Troy B; Varady, Nathan H; Rajaee, Sean; Chen, Antonia F (Journal of bone and joint surgery. American volume, 2020)
Trends in racial disparities in total joint arthroplasty (TJA) care have been documented from 1991 to 2008. However, it remains unknown whether numerous national and orthopaedic-specific efforts to reduce these disparities have been successful. The purpose of this study was to investigate trends in racial disparities in TJA utilization and perioperative metrics between black and white patients in the U.S. from 2006 to 2015. The National Inpatient Sample (NIS) was queried to identify black and white patients who underwent primary total knee arthroplasty (TKA) or primary total hip arthroplasty (THA) between 2006 to 2015. Utilization rates, length of stay in the hospital (LOS), discharge disposition, and inpatient complications and mortality were trended over time. Linear and logistic regression analyses were performed to assess changes in disparities over time. From 2006 to 2015, there were persistent white-black disparities in standardized utilization rates and LOS for both TKA and THA (p < 0.001 for all; ptrend > 0.05 for all). Moreover, there were worsening disparities in the rates of discharge to a facility (rather than home) after both TKA (white compared with black: 40.3% compared with 47.2% in 2006 and 25.7% compared with 34.2% in 2015, ptrend < 0.001) and THA (white compared with black: 42.6% compared with 41.7% in 2006 and 23.4% compared with 29.2% in 2015, ptrend < 0.001) and worsening disparities in complication rates after TKA (white compared with black: 5.1% compared 6.1% in 2006 and 3.9% compared with 6.0% in 2015, ptrend < 0.001). There were persistent, and in many cases worsening, racial disparities in TJA utilization and perioperative care between black and white patients from 2006 to 2015 in the U.S. These results were despite national efforts to reduce racial disparities and highlight the need for continued focus on this issue. Although recent work has shown that elimination of racial disparities in TJA care is possible, the present study demonstrates that renewed efforts are still needed on a national level.